Branding the Middle East : Communication Strategies and Image Building from Qom to Casablanca - Wippel, Steffen (2023)
This edited volume investigates place, product, and personal branding in the Middle East and North Africa, including some studies from adjacent regions and the wider Islamicate world. Going beyond simply presenting logos and slogans, it critically analyses processes of strategic communication and image building under general conditions of globalisation, neoliberalisation, and postmodernisation and, in a regional perspective, of lasting authoritarian rule and increased endeavours for "worlding." In particular, it looks at the multiple actors involved in branding activities, their interests and motives, and investigates tools, channels, and forms of branding. A major interest exists in the entanglements of different spatial scales and in the (in)consistencies of communication measures. Attention is paid to reconfigurations of certain images over time and to the positioning of objects of branding in time and space. Historical case studies supplement the focus on contemporary branding efforts. While branding in the Western world and many emerging economies has been meticulously analysed, this edited volume fills an important gap in the research on MENA countries.